Generalized strongly almost summable difference sequences of order m defined by a sequence of moduli - Bektaş, Çi?dem Asma; Çolak, Rifat (Walter de Gruyter GmbH, 2007)
In this paper we introduce some new sequence spaces by using a sequence of moduli F = (fk) , give some topological properties and inclusion relations related to these sequence spaces. We also give the ?-dual of [?, F,p]?(?m). © 2007 Warsaw University. All rights reserved.
Keywords: Difference sequence; Sequence of moduli